Penguasaan Materi Media Pembelajaran dalam Upaya Menyiapkan Guru yang Mampu Menyelenggarakan Pembelajaran yang Mendidik - Emma Himayaturohmah (Jurnal Penjaminan Mutu, 2019)
The problem of this study is the low mastery of computer-based learning media or information technology for Madrasah Ibtidaiyah teachers. The low mastery capacity of learning media directly influences the low competency in conducting educational education. Current curriculum demands teachers are required to master the use of technology in classroom learning. The purpose of this study was to determine the mastery of learning media materials and competencies in conducting educational learning. This research is a field research quantitative descriptive approach. The subjects in this study were Information and Communication Technology-Based Learning Media Training Participants for Teachers of Islamic Education in Kuningan District, West Java Province. Data collection techniques were carried out using questionnaires, observation, interviews and documentation studies. The results showed that mastery of learning media material had an average value of 85.86 which was categorized as good. While mastery of competency in organizing learning that educates has an average value of 80.5 which means it has a good category.